Penjajagan Awal Penerapan New Public Management dalam Administrasi Kabupaten - Wibawa, Samodra (Jurnal Ilmu Sosial dan Ilmu Politik, 2002)
The popularity of New Public Management in the developed countries raises a question whether such a concept applicable in the Third World context. Relies on three focuses group discussion involving local bureaucrats, this article shows the desirability of New Public Management as model of local public administration, despite a strong awareness of the challenge they have to encounter.